Differences in pH influence the fate of CO2 in plants. Issue 3 (20th February 2019) - Law, Simon R.
Abstract : Soils represent the largest and most stable carbon pools on Earth, exceeding even the carbon aggregate found in the atmosphere and global phytomass. However, our understanding of how CO2 travels from the soil to the atmosphere, and the role of plants in this journey, is not fully understood. An article in this issue of Physiologia Plantarum (Shimono et al. 2019) sheds light on this process and unearths the dramatic effect pH can have on the fate of CO2 in plants.